Association of serum adropin with risk and severity of diabetic peripheral neuropathy in patients with type 2 diabetes mellitus - Nearmeen M Rashad; Hanan M Sabry; Samir A Afifi; Maha A Fathy (SpringerOpen, 2019)
Background Diabetic peripheral neuropathy (DPN) is the major microvascular complication of type 2 diabetes mellitus (T2DM). Adropin is a peptide hormone that has essential roles in metabolic homeostasis and the pathogenesis of T2DM and its complications. This study was designed to estimate serum adropin levels in patients with T2DM in correlation with risk factors of DPN. The authors also aimed to investigate the association between serum adropin level and clinical and electrophysiological tests of DPN. Patients and methods This case-control study enrolled 100 patients with T2DM (40 diabetic cases without DPN and 60 diabetic cases with DPN) and 50 controls. All participants were subjected to a complete neurological examination. The motor and sensory conduction velocities of the median nerve, ulnar nerve, and common peroneal nerve were measured. The severity of DPN was assessed by Toronto clinical scoring system (TCSS). Serum adropin levels were assessed using an enzyme-linked immunosorbent assay. Results Our results revealed decreased circulating serum adropin levels in patients with T2DM (3.5±1.2), especially diabetic patients with DPN (3.1±1.07), compared with controls (6.1±0.89). There is a negative correlation between serum adropin level and TCSS as well as electrophysiological tests: motor nerve conduction velocity of median and ulnar nerve, sensory nerve conduction velocity of median and ulnar nerve, compound muscle action potential amplitude (median and ulnar nerve), and sensory nerve action potential amplitude (median, ulnar, and perception threshold nerve) (P<0.001FNx01). Conclusion Diabetic patients with DPN had lower values of serum adropin than diabetic patients without DPN, and serum adropin levels were negatively correlated with metabolic risk factors, TCSS, as well as electrophysiological tests of DPN.